2019
DOI: 10.3389/fmicb.2019.00241
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Leaf- and Root-Associated Communities of Bacteria and Fungi Across 33 Plant Orders in a Grassland

Abstract: In terrestrial ecosystems, plants interact with diverse taxonomic groups of bacteria and fungi in the phyllosphere and rhizosphere. Although recent studies based on high-throughput DNA sequencing have drastically increased our understanding of plant-associated microbiomes, we still have limited knowledge of how plant species in a species-rich community differ in their leaf and root microbiome compositions. In a cool-temperate semi-natural grassland in Japan, we compared leaf- and root-associated microbiomes ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 85 publications
(100 reference statements)
1
33
0
Order By: Relevance
“…Microbiological data collected from lettuce and reported in the literature provides evidence that different parts of the plant, i.e., leaves and roots support distinct microbial communities (Ibekwe and Grieve, 2004;Toju et al, 2019). While our culture based isolation of bacteria recovered a few species unique to leaves many of the isolates present on the phyllosphere were also present in the roots.…”
Section: Discussionmentioning
confidence: 49%
“…Microbiological data collected from lettuce and reported in the literature provides evidence that different parts of the plant, i.e., leaves and roots support distinct microbial communities (Ibekwe and Grieve, 2004;Toju et al, 2019). While our culture based isolation of bacteria recovered a few species unique to leaves many of the isolates present on the phyllosphere were also present in the roots.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies indicated that plant endophytes showed significant host preferences ( Toju, Kurokawa & Kenta, 2019 ; Yao et al, 2019 ). Different plant species sharing similar environments recruit different microbial communities in roots ( Aleklett et al, 2015 ), which may be related to the metabolic characteristics of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Plant compartments/organs serve as specific nichesenvironmental surroundings that affect their growth and performance -colonized by a distinctive assemblage of microbial taxa (Muller et al, 2016;Beckers et al, 2017;Zheng and Gong, 2019). The most frequently studied plant organs are roots and leaves (Muller et al, 2016;Toju et al, 2019). Bamboo leaves and roots have different microbiota: root endophytic bacteria were dominant by Bacillus (Han et al, 2009), while the leafdwelled endophytes were mainly composed by Staphylococcus (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%